Validation of albumin platelet product as a non-invasive fibrosis staging tool in patients with chronic HCV-related liver disease - Maha Elsabaawy; Mohamed Eissa; Ahmed Shaban; Madiha Naguib (Scientific Reports, 2025)
Abstract Background and aim: The Albumin Platelet Product (APP) has emerged as a promising non-invasive biomarker for fibrosis staging in chronic liver disease (CLD). This cross-sectional study aims to evaluate the effectiveness of APP compared to established non-invasive markers of fibrosis in an Egyptian cohort with HCV-related CLD. Methods: 580 participants were assessed across different fibrosis stages (F0-F4) to analyze the relationship between APP and liver fibrosis. APP was compared with FIB-4 and APRI scores for diagnostic performance. Results: The study included 580 patients with HCV-related CLD (mean age: 37.6 ± 9.66 years; 74.3% males). APP proved superiority in identifying liver cirrhosis (F4) at Cut-off values ≤ 0.59 with 81% sensitivity, 63.6% specificity (p < 0.001). APP showed a significant correlation with fibrosis stages, with an AUC of 0.920 (95% CI: 0.888–0.953) for distinguishing F4 from F0-F3 surpassing both FIB4 and APRI scores. However, FIB-4 proved superiority in distinguishing advanced fibrosis (F ≥ 3) with AUC of 0.899 (95% CI: 0.871–0.927) compared to APP with AUC of 0.87 (95% CI: 0.84–0.90), respectively. Multivariate analysis confirmed APP as an independent predictor of fibrosis (OR: 0.997, 95% CI: 0.995–0.998; p < 0.001). Conclusion: APP showed the highest performance in predicting cirrhosis, suggesting its potential as a simple, non-invasive marker for identifying patients with advanced liver disease. Its integration into clinical practice may enhance early detection and risk stratification in chronic HCV-related fibrosis. However, further multicenter, longitudinal studies are required to validate its efficacy across diverse populations and other liver disease etiologies.